Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/toxics11040325
|View full text |Cite
|
Sign up to set email alerts
|

Per- and Polyfluoroalkyl Substances and Breastfeeding as a Vulnerable Function: A Systematic Review of Epidemiological Studies

Abstract: Milk formation in the breast during breastfeeding is a complex hormonally regulated process, potentially sensitive to the effects of endocrine-disrupting chemical exposures. The environmental chemicals, per- and polyfluoroalkyl substances (PFAS) are known endocrine disruptors. PFAS exposure have been associated with insufficient mammary gland development in mice and reduced breastfeeding duration in humans. The aim of this review was to gather the epidemiological evidence on the association between PFAS exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 82 publications
0
10
2
Order By: Relevance
“…In utero exposure to persistent organic pollutants such as PFAS is associated with negative outcomes in pregnancy, after birth, and later in life [ 32 ]. PFAS have been associated with increased incidence of gestational diabetes, childhood obesity, preeclampsia, reduced lactation duration, and fetal growth restriction [ 189 196 ]. Unfortunately, the toxicological effects of PFAS as a mixture are generally unknown [ 197 ].…”
Section: General Discussion and Future Directionsmentioning
confidence: 99%
“…In utero exposure to persistent organic pollutants such as PFAS is associated with negative outcomes in pregnancy, after birth, and later in life [ 32 ]. PFAS have been associated with increased incidence of gestational diabetes, childhood obesity, preeclampsia, reduced lactation duration, and fetal growth restriction [ 189 196 ]. Unfortunately, the toxicological effects of PFAS as a mixture are generally unknown [ 197 ].…”
Section: General Discussion and Future Directionsmentioning
confidence: 99%
“…29 Associations differed by specific PFAS but were most consistent for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA). 29 All but one of the previous studies were conducted in Scandinavian countries. The sole US study was conducted in a population having higher serum PFOA concentrations relative to the general US population.…”
Section: Introductionmentioning
confidence: 99%
“…6,22 Several studies have examined associations between pregnancy PFAS concentrations and breastfeeding duration. 7,[23][24][25][26][27][28][29] In a recent systematic review of the six previous epidemiologic studies on this topic, five of the six found higher PFAS concentrations were associated with shorter breastfeeding duration. 29 Associations differed by specific PFAS but were most consistent for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated in a pilot study that circulating polyfluoroalkyl substances (PFASs) were associated with the HBM lipid composition, with high exposure being associated with reduced nutritional quality of HBM, with reduction in total lipid content, reduced concentration of polyunsaturated FAs (PUFAs), such as lipids containing docosahexaenoic acid- and arachidonic acid, while lipid containing saturated FAs were increased with higher PFAS exposure . PFASs are industrial chemicals that are used in a wide range of industrial and consumer applications, and their persistence in the environment has led to their widespread distribution in water, soil, wildlife, and humans. Epidemiological studies indicate a potential inverse relationship between maternal PFAS levels and duration of breastfeeding. Studies in animal models have shown that exposure to PFAS during gestation can lead to impaired mammary differentiation and stunted mammary epithelial development in offspring . Together, the current data suggest that accumulated PFAS exposure may disrupt lactation and alter the composition of breast milk.…”
Section: Introductionmentioning
confidence: 99%